Institutions, unionization and voice: The relative impact of context and actors on firm level practice. (May 2015) - Brewster, Chris; Wood, Geoffrey; Goergen, Marc
Trade unions provide a voice in the way firms are run, an input into reward systems and increased security of employment. But these vary with national context. Using transnational survey evidence, this article explores the relative impact of setting, and of unions and collective bargaining, on these issues. It is found that, irrespective of context, organizations are significantly more likely to make use of compulsory redundancies in the absence of unions and collective bargaining. However, in other areas, the impact of unions appeared less pronounced than that of the wider context. The article explores the reasons behind this, and the broader policy implications thereof.